Seni Musik Tradisional Tongtek sebagai Sarana Peningkatan Kreativitas dan Interaksi Sosial Pemuda IKRAR CR13 di Desa Kecapi Telahap - Delfi Novelia Pratiwi; Wasis Wijayanto (FKIP, Universitas Palangka Raya, 2026)
This study aims to identify the traditional Tongtek music art as a means of increasing creativity and social interaction among IKRAR CR13 youth in Kecapi Telahab Village. This traditional musical art should generally serve as one of the media to support the development of creativity among the younger generation and to train their social interaction skills. In addition, creativity also plays an important role in improving individual intelligence and enriching cooperative experiences through positive social interaction. This research used a qualitative method. The research subjects were the IKRAR CR13 youth group in Kecapi Telahab Village, Tahunan District, Jepara Regency. Data analysis in this study used a descriptive qualitative approach adjusted to the needs of the research. This descriptive qualitative method was used to explain the phenomenon under study in depth. Data were collected through observation, interviews, and literature studies. Based on the results of this study, the existence of traditional Tongtek music art contributed to an increase in children’s creativity and social interaction, as evidenced by developments and changes in knowledge, skills, and attitudes among children as the next generation of the IKRAR CR13 youth group in Kecapi Telahab Village.